Okay for now - Schmidt, Gary D. (Sandpiper, 2011)
As a fourteen-year-old who just moved to a new town with no friends, an abusive father, and a louse for an older brother, Doug Swieteck has all the stats stacked against him until he finds an ally in Lil Spicer--a fiery young lady. Together, they find a safe haven in the local library, inspiration in learning about the plates of John James Audubon's birds, and an adventure on a Broadway stage.